Role of Fibulin 3 in Aging‐Related Joint Changes and Osteoarthritis Pathogenesis in Human and Mouse Knee Cartilage. Issue 3 (27th February 2017) - Hasegawa, Akihiko; Yonezawa, Tomo; Taniguchi, Noboru; Otabe, Koji; Akasaki, Yukio; Matsukawa, Tetsuya; Saito, Masahiko; Neo, Masashi; Marmorstein, Lihua Y.; Lotz, Martin K.
Abstract : Objective: The EFEMP1 gene encoding fibulin 3 is specifically expressed in the superficial zone (SZ) of articular cartilage. The aims of this study were to examine the expression patterns of fibulin 3 in the knee joints during aging and during osteoarthritis (OA) and to determine the role of fibulin 3 in the pathogenesis of OA. Methods: Immunohistochemical analysis was performed on normal and OA knee cartilage samples from humans and mice. Experimental OA was induced in wild‐type and fibulin 3 −/− mice, and the severity of OA was evaluated by histologic scoring. To examine fibulin 3 function, human chondrocyte monolayer cultures were transfected with small interfering RNA (siRNA), followed by quantitative polymerase chain reaction and Western blot analyses. Human bone marrow–derived mesenchymal stem cells (BM‐MSCs) were transduced with an EFEMP1 lentivirus and analyzed for markers of chondrogenesis. Results: Fibulin 3 was specifically expressed in the SZ of normal knee joint cartilage from humans and mice, and the expression levels declined with aging. Both aging‐related OA and experimental OA were significantly more severe in fibulin 3 −/− mice compared with wild‐type mice. Fibulin 3 expression was high in undifferentiated human BM‐MSCs and decreased during chondrogenesis. Suppression of fibulin 3 by siRNA significantly increased the expression of SOX9, type II collagen, and aggrecan in human articular chondrocytes, while overexpression of fibulin 3 inhibited chondrogenesis in BM‐MSCs. Conclusion: Fibulin 3 is specifically expressed in the SZ of articular cartilage and its expression is reduced in aging and OA. Fibulin 3 regulates differentiation of adult progenitor cells, and its aging‐related decline is an early event in the pathogenesis of OA. Preventing aging‐associated loss of fibulin 3 or restoring it to normal levels in SZ chondrocytes has the potential to delay or prevent the onset of OA.